Mastosit Perivaskuler Berperan Sebagai Vasodilator Pembuluh Darah pada Mesenterium Tikus - Ibrahim, Mohamad Nur; Soleh, Miftahu; Widjajanto, Edi (Fakultas Kedokteran Universitas Brawijaya, 2009)
Mastocyt degranulated can cause vasodilatation of blood vessels, but it is unclear whether there is a relationship between the number of mastocyt with a diameter of blood vessels. This study aims to determine the relationship between the number of mastocyt pherivascular and diameter of blood vessels. This research is in vivo exploratory research in Wistar rat mesentery which was sensitated with ovalbumin. The diameter of blood vessels at mesentery preparate were measured microscopically using a micrometer scale standards. At large diameter of blood vessels (2.860 ± 0.348), the number of mastocyt was 12.3 ± 2.3. At medium diameter of blood vessel (1.276 ± 0.198), the number of mastocyt was 4.4 ± 0.5. Blood vessels with small diameter (0.961 ± 0.043), the number of mastocyt was 3.5 ± 1.3. Calculations area on the microscope visual field was divided into four areas (counting area), there were zone 1, zone 2, zone 3 and zone 4. Statistical analysis showed that the correlation between the number of mastocyt at zone 1 and the diameter of blood vessels was 0,904 at 1% significance level. Similar to that at zone 2 (r=0,892), zone 3 and zone 4 (r=0,940). We conclude there was a significant relationship between the number of mastocyt and the diameter of blood vessels. Keywords: mastocyt pherivascular, diameter of blood vessels